NSCA's guide to program design - Hoffman, Jay (Illinois : Human Kinetcs, 2012)
Presents the information, guidance and protocols from respected scientists and practitioners in strength and conditioning programme design. Developed by the National Strength and Conditioning Association (NSCA), this text offers a scientific basis for developing training programmes for specific athletes at specific times of the year.
Athlete needs analysis / William J. Kraemer -- Athlete testing and program evaluation / Jay R. Hoffman -- Dynamic warm-up / Avery D. Faigenbaum -- Resistance training / Nicholas A. Ratamess -- Power training / Robert U. Newton -- Anaerobic conditioning / Jay R. Hoffman -- Endurance training / Joel T. Cramer -- Agility training / Lee E. Brown -- Speed training / Jay R. Hoffman -- Balance and stability training / Nejc Sarabon -- Training integration and periodization / G. Gregory Haff -- Training program implementation / Jay R. Hoffman
Includes bibliographical references and index.
Keywords: PHYSICAL EDUCATION AND TRAINING